N. America - Woodward, E. F.
This map shows North and Central America and the surrounding areas. Countries are shaded in different colors (with all of Central America labeled "Guatemala"). Cities and towns are marked based on population (the key is at the bottom of the map). Bodies of water and geographic features are marked (with relief based on hachures) as well as Russian and British possessions and the locations of some Native American tribes. An illustration of an Indian near a lake is in the lower left corner.